Answer:
(6y - 1)(6y + 1)
Step-by-step explanation:
To factorize completely, we may adopt the difference of 2 squares approach. The theory states that difference of two square is the product of the difference of the number and the sum of the numbers.
Such that
a² - b² = (a - b) (a + b)
Hence 36y² - 1
= 6²y² - 1²
= (6y)² - 1²
= (6y - 1)(6y + 1)
Answer:
There is no equal sign.
Step-by-step explanation:
There is no equal sign to make it an algebraic equation.
The surface area of the right triangular prism is 270 sq ft
<h3>Total surface ara of the prism</h3>
The total surface area of the prism is the sum of all the area of its faces
For the two triangles
A = 2(0.5bh)
A = bh
A = 7 * 12 = 84 sq.ft
For the two rectangles
A = 2lw
A = 2(6*12)
A = 2 * 72 = 144 sq.ft
For the third triangle;
Area 6ft * 7ft
Area = 42 sq.feet
Taking the sum of the areas
TSA = 84 + 144 + 42
TSA = 270 sq ft
Hence the surface area of the right triangular prism is 270 sq ft
Learn more on surface area of prism here; brainly.com/question/1297098
$9.99 is 15% if $66.60 which totals up to $76.59.
Answer a-$10.05 estimate
Answer:
36-2n<1/3n+15
Step-by-step explanation:
There are multiple solutions. One solution is 30. Because 30 times 2 is 60 and 36-60 is less than 1/3 of 30 (10) plus 15.